Defining fashion film festival: A terminological issue - VLADISLAV V. ANANISHNEV / В.В. АНАНИШНЕВ (Наука телевидения)
This article examines the terminology surrounding international fashion film festivals. While a relatively recent phenomenon in Russia (officially emerging in 2018), existing Russian research on film festivals largely ignores this specific area. The widely used English term “fashion film festival” lacks a standardized Russian equivalent and is not defined in Russian film festival legislation. This article chronologically analyzes prominent international fashion film festivals, focusing on their goals, market position, founding, brand partnerships, and cinematic interactions, as documented in press and international research. This analysis clarifies the meaning of “international fashion film festival” in the Russian context.